Aplikasi Matriks Leslie untuk Memproyeksi Jumlah Penduduk Perempuan dan Laju Pertumbuhan Penduduk di Kabupaten Banyumas Tahun 2027 - Pratiwi, Yuliyanti Dian; Hidayati, Nurul; Mariska, Melli; Sagita, Sarlita Indah; Gusaynsan, Axioma Elmonura (Proceedings Series on Physical & Formal Sciences, 2023)
BPS knows the population and the rate of population growth, namely using a population census that is carried out once every 10 years, because this timeframe is the right time to see the birth rate and death rate for an area. So it takes a long time to know the amount of population growth and population growth rate. Based on BPS data for Banyumas Regency for 2021, the population is 1,789,630 people, the population growth rate is 95%. And in 2022 the population will be 1,806,013 people, the population growth rate is 93%. So for 1 year from 2021 to 2022 there will be an increase of 16,383 people, based on data from BPS the number of Banyumas districts has increased. The Leslie Matrix is ??one of the mathematical tools used to model the growth and changes in populations of living things, so that it can assist BPS in predicting population numbers and population growth rates at a time. From Leslie's matrix calculations, the prediction for the female population in Banyumas Regency in 2027 is 985,304 people. And the result of calculating the dominant eigenvalue is ?=1.23 which shows that population growth is increasing.